The Effect of Implementing EMR on User Acceptance EMR Based on UTAUT 2 theory In Hospital - Bachtiar, Silvani; Baktiar, Rahmat; Sedionoto, Blego (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The Ministry of Health requires every health facility in Indonesia to maintain electronic medical records based on Minister of Health Regulation (Permenkes No.24/2022). However, the use of Electronic Medical Records (EMR) in Indonesia still finds many obstacles in user acceptance based on the Unified Theory of Acceptance and Use of Technology (UTAUT) 2 method Objective : This research aims to assess the implementation of EMR on user acceptance in hospitals. Research Methods/ Implementation Methods : This research uses a literature review method by reviewing 30 journal articles published between 2020 and 2024, which were retrieved via Google Scholar Results : The research results show that performance expectations, effort expectations, social influence, facilitating conditions, hedonic motivations, price values and habits influence the behavior intentions and Use Behavior of Electronic Medical Record users. In several studies, there are moderating variables such as age, gender and work experience that influence the relationship between constructs that build user intentions and behavior.